Manual of helminthiasis - Ryabokon, E. V.; Onischenko, T. E.; Ushenina, L. O.; Furyk, E. A.; Mashko, O. P. (Zaporozhye state medical university, 2013)
Helminths are worms causing a wide variety of diseases globally called helminthiases. Helminthiases almost only occur in developing countries, particularly in areas where sanitation is low sanitation. This manual reviews current and recent information concerning pathogenic helminths, the characteristics of their eggs and sanitary strategies controlling them. The offered manual of Helminthisms will help students to learning skills of inspection, diagnostic thought, planning medical and prophylactic measures at infectious pathology in people.